Being Poorer than the Rest of the Neighbourhood: Relative Deprivation and Problem Behaviour of Youth - Jaap Nieuwenhuis; Maarten van Ham; Rongqin Yu; Susan Branje; Wim Meeus; Pieter Hooimeijer (Institute for the Study of Labor (IZA), 2016)
According to the neighbourhood effects hypothesis, there is a negative relation between neighbourhood wealth and youths' problem behaviour. It is often assumed that there are more problems in deprived neighbourhoods, but there are also reports of higher rates of behavioural problems in more affluent neighbourhoods. Much of this literature does not take into account relative wealth. Our central question was whether the economic position of adolescents' families relative to the neighbourhood in which they lived, was related to adolescents' internalising and externalising problem behaviour. We used longitudinal data for youths between 12-21 years of age, combined with population register data. We employ between-within models to account for time-invariant confounders, including parental background characteristics. Our findings show that for adolescents, moving to a more affluent neighbourhood was related to increased levels of depression, social phobia, aggression, and conflict with father and mother. This could be indirect evidence for the relative deprivation mechanism, but we could not confirm this, and we did not find any gender differences. The results do suggest that future research should further investigate the role of individuals' relative position in their neighbourhood in order not to overgeneralise neighbourhood effects and to find out for whom neighbourhoods matter.
Keywords: I30; R23; 330; neighbourhood effects; externalising problems; internalising problems; relative deprivation; adolescents; residential mobility